Increased cancer risk in polycystic ovary syndrome: An (un)sympathetic connection?. (January 2020) - Mravec, Boris; Tibensky, Miroslav
Abstract: Women with polycystic ovary syndrome (PCOS) have been shown to have a higher incidence of cancer. It is suggested that several factors, including hyperinsulinemia, dyslipidemia, raised estrogen levels, chronic inflammation, and reduced apoptosis are responsible for this association. However, in this paper we propose the hypothesis that increased sympathetic activity may represent an important factor that interconnects PCOS and cancer. This hypothesis is based on two facts: a) in women with PCOS is found sympathetic hyperactivity and b) recent data showing a stimulatory effect of the sympathetic system on cancer initiation, progression, and development of metastases. If our hypothesis is correct, then new preventive approaches might be used to reduce cancer risk in women with PCOS.